Adopting the Concepts of Distributive and Compensatory Justice as an Approach to Determining Optimal Tax Treatments for Corporate Donations: A Justified View - Younis A. Battal Saleh (JAF (Journal of Accounting and Finance), 2026)
This study examines the determination of tax treatment for corporate donations by applying the concepts of distributive justice and compensatory justice. The objective is to develop a more rational and equitable framework that aligns tax policy with principles of fairness among corporations and stakeholders, including government, shareholders, and society, while preserving the integrity of corporate social responsibility (CSR). Using a conceptual and analytical approach, the study evaluates corporate donations based on several criteria, including their impact on financial performance, their social and environmental implications, and their role under different market conditions. Based on this evaluation, the study proposes seven alternative scenarios for classifying corporate donations and determining appropriate tax treatments grounded in either distributive justice or compensatory justice. The findings suggest that uniform tax policies, whether granting or denying tax incentives, may fail to achieve fairness across different contexts. Instead, a differentiated approach based on the underlying characteristics of corporate donations provides a more balanced and justifiable basis for tax policy design. This study contributes to the literature by offering a conceptual framework that integrates justice-based perspectives into tax policy analysis and provides practical insights for policymakers in developing more equitable and context-sensitive tax systems.